Analysis of the surveillance results of avian influenza in the external environment of huzhou city from 2017 to 2023 - Yuda Wang; Jianyong Shen; Guangtao Liu; Ziqi Jiang; Hang Liu; Tao Yu; Zhuoxin Ying; Junfen Lin; Yan Liu (PLoS ONE, 2025)
Background Avian influenza is an infectious disease of birds caused by the influenza A virus, which can infect a variety of domestic,wild birds and even cross the species barrier and infect humans.To understand the contamination of avian influenza virus in the external environment of poultry in Huzhou City from 2017 to 2023 and to assess the risk of human infection with avian influenza. Methods A total of 3,400 environmental specimens from five types of venues in Huzhou City were collected and tested for influenza A virus nucleic acid using fluorescent reverse transcription polymerase chain reaction (RT-PCR). Results From 2017 to 2023, with 15.44% overall positive rate of influenza A virus. The predominant subtype of avian influenza virus was H9 (accounting for 54.67%). The peak of positive influenza virus detection rates occurred in winter and spring seasons every year. The venue with highest positive rate was poultry slaughtering and processing plants (41.83%), followed by urban and rural live poultry markets (35.48%); among all types of specimens, the highest positive rate was detected in swab specimens from the surfaces of poultry slaughtering or display tables (47.37%), followed by wastewater from poultry washing (45.83%), and surfaces of cages (27.65%). Conclusion The contamination of avian influenza virus in the poultry environment in Huzhou City is relatively severe, with diverse subtypes. There is a potential risk of human infection with avian influenza virus, and real-time monitoring of avian influenza virus in the poultry environment needs to be strengthened.